Rural-urban difference in meeting the need for healthcare and food among older adults: evidence from India - Jyoti Das; Sampurna Kundu; Babul Hossain (BMC, 2023)
Abstract Background Due to changes in demographic and epidemiological scenarios, and the gradual increase in the older population, India is yet to prepare for rising nutrition and health-related issues among older adults in the coming decades. While the process of ageing and its associated aspect has been found to have an urban-rural divide. Thus, this study examines rural/urban differences in unmet needs for food and healthcare among Indian older adults. Methods A sample of 31,464 older adults aged 60 years and above were considered in the study from the Longitudinal and Ageing Survey of India (LASI). The bivariate analysis was done using the sampling weights. Logistic regression and decomposition analysis was used to explain the rural-urban gap in the unmet needs for food and healthcare among Indian older adults. Results Rural older adults were more vulnerable to meeting the need for health and food than their urban counterparts. While factors that contributed majorly to the difference in unmet need for food between urban and rural were education (34.98%), social group (6.58%), living arrangements (3.34%) and monthly per capita expenditure (MPCE) (2.84%). Similarly, for the unmet need for health, the factors that contributed the most to the rural-urban gap are education (28.2%), household size (2.32%), and MPCE (1.27%). Conclusion The study indicates more vulnerability among rural older adults than compared to urban older individuals. The targeted policy-level efforts should be initiated considering the economic and residential vulnerability identified in the study. There is a need for primary care services that can provide targeted help to older adults in rural communities.